Dots - Armleder, John (Three Star Books, 2024)
John Armleder is renowned for his diverse and eclectic approach, employing materials ranging from furniture to neon lights without hierarchical distinctions. Among his recurrent patterns, polka dots challenge traditional distinctions between high art and decoration. Armleder uses dots to bring everyday motifs into fine art, showcasing versatility across paintings, installations, and furniture. Since the late 1970s, he has transformed dots from basic design elements into a nuanced system of representation, inspired by avant-garde figures like Francis Picabia. For Armleder, dots are as important as the infinite choice of ties with repetitive motifs that he wears, both serving as symbols of his playful and multifaceted artistic identity. ... The initial inspiration for the production of "ƧTOꓷ" came from the artist’s 2016 print titled "DIVISIONS," which provided the pattern used as the foundation for the book. The concept evolved to blend the artist’s dot paintings with his fascination for disco balls, incorporating mirror paper into the design. As you flip through the pages of ƧTOꓷ, a captivating illusion emerges. The combination of holes and mirrored surfaces creates a magical interplay of "plein et vide" (full and empty), where the reflections give the impression of shifting spaces and layers. https://threestarbooks.com/JOHN-ARMLEDER-STOD-1
Leporello
Das Wort "dots" ist spiegelverkehrt gedruckt.
In vom Künstler gestaltetem Schuber
Auflage: 20 nummerierte, signierte Exemplare
Keywords: Künstlerbuch